2009
DOI: 10.1177/1096348009350624
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Quality of Food, Service, and Physical Environment on Customer Satisfaction and Behavioral Intention in Quick-Casual Restaurants: Moderating Role of Perceived Price

Abstract: This study examined the relationships between three determinants of quality dimensions (predictors: food, service, and physical environment), price (moderator), and satisfaction and behavioral intention (criterion) in quick-casual restaurants. Despite the importance of foodservice quality, academics and managers know relatively little about how the combined effects of quality (food, service, and physical environment) elicit customer satisfaction which, in turn, affects behavioral intention. Hierarchical multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
432
6
43

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 576 publications
(562 citation statements)
references
References 58 publications
(77 reference statements)
48
432
6
43
Order By: Relevance
“…The National Council of the Green Consumers Network (2012) in Korea reported that many mobile phone subscribers were dissatisfied with the level and types of service charges. Ryu and Han (2010) found that the perceived price has a significant effect on the relationship between quality and customer satisfaction in the quick-casual restaurant industry. That is, customers' perception of a reasonable price enhances the effect of service quality on customer satisfaction.…”
Section: Perceived Pricementioning
confidence: 99%
See 3 more Smart Citations
“…The National Council of the Green Consumers Network (2012) in Korea reported that many mobile phone subscribers were dissatisfied with the level and types of service charges. Ryu and Han (2010) found that the perceived price has a significant effect on the relationship between quality and customer satisfaction in the quick-casual restaurant industry. That is, customers' perception of a reasonable price enhances the effect of service quality on customer satisfaction.…”
Section: Perceived Pricementioning
confidence: 99%
“…Several researchers agree to the combined effects of perceived value and quality on satisfaction (Caruana, Money, and Berthon, 2000;Ryu and Han, 2010). Caruana et al (2000) examined that perceived value has a significant moderating effect on the relationship between service quality and customer satisfaction.…”
Section: Perceived Valuementioning
confidence: 99%
See 2 more Smart Citations
“…Although many research studies have emphasized the importance of perceived value and the role of perceived price in that relationship, a limited number of empirical research has investigated the infl uence of perceived price on consumer behavior in the service industry (Ryu & Han, 2010 Zeithaml (1988) dealt with the costs of search, waiting, etc. -in short, all eff orts, risks, and insecurities connected to the acquisition and use of a product.…”
Section: Antecedents Of Perceived Valuementioning
confidence: 99%